ANALISIS KONSEP PEMBELAHAN SEL DALAM BUKU TEKS BIOLOGI SMA - Yuliarsih, Asih; Candramila, Wolly; Wahyuni, Eko Sri (Universitas Tanjungpura, 2025)
Textbooks serve as one of the primary learning resources in senior high school biology education. However, various studies have revealed the presence of conceptual inaccuracies and misconceptions in biology textbooks, particularly on complex topics such as cell division. This study aims to analyze the availability and conceptual accuracy of cell division content in four of the most commonly used grade XII biology textbooks in senior high schools in Pontianak. Using a qualitative descriptive approach with content analysis, date were collected through interviews with 27 biology teachers and analysis of textbook content based on nine essential concepts of cell division. The findings indicate that only one textbook presents all nine concepts, while the others present between six and seven concepts. Moreover, all textbooks exhibit potential misconceptions, especially on the topic of gametogenesis in higher plants. The types of misconceptions identified include oversimplification, overgeneralization, and misidentification. These results highlight the need for rigorous evaluation of biology textbooks to ensure both content completeness and scientific accuracy. This study provides valuable insights for educators, textbook authors, and policymakers in improving the quality of biology education through more accurate and pedagogically sound learning materials.